2018
DOI: 10.1002/mame.201800603
|View full text |Cite
|
Sign up to set email alerts
|

A Thermo‐ and Moisture‐Responsive Zwitterionic Shape Memory Polymer for Novel Self‐Healable Wound Dressing Applications

Abstract: Developing wound dressings that have strong adhesion strength without causing any conglutination to the wound site is still challenging. Herein, is proposed that zwitterionic shape memory polymers can be applied as promising candidates for wound dressing. Sulfobetaine methacrylate (SBMA) is copolymerized with 2,3‐dihydroxypropyl methacrylate (DHMA) in the presence of boric acid as a cross‐linking agent. The prepared material exhibits multi‐stimuli responsive shape memory behaviors: it can rapidly return to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…136 Li et al also reported a water-triggered shape-memory behavior for a zwitterionic polymer. 137 Again, moisture absorption led to breaking of ionic interactions and a plasticizing effect, which allows an improved strain release and recovery to the permanent shape.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…136 Li et al also reported a water-triggered shape-memory behavior for a zwitterionic polymer. 137 Again, moisture absorption led to breaking of ionic interactions and a plasticizing effect, which allows an improved strain release and recovery to the permanent shape.…”
Section: Reviewmentioning
confidence: 99%
“…144 It is worth mentioning that moisture can act as a local plasticizer at the cut surfaces, increasing local mobility and liberating free ionic groups to heal local damage. 137 For instance, Wen et al designed zwitterionic PU bearing pyridinium and sulfonate moieties. 148 Within such systems, a high zwitterion amount led to higher self-healing performance (from ca.…”
Section: Self-healingmentioning
confidence: 99%
See 1 more Smart Citation
“…fabricated a copolymerized novel zwitterionic shape memory polymer composed of sulfobetaine methacrylate (SBMA) and diol acrylate monomer (dihydroxypropyl methacrylate, DHMA) for wound healing applications. [ 50 ] In this report, boric acid was added as crosslinkers to the polymeric complex. Shape memory behavior for this hydrogel dressing was created from electrostatic interactions of PSBMA chains with dynamically bonded boron esters, which are triggered by either temperature or absorbing moisture.…”
Section: Evolutionary Trend Of Wound Dressingsmentioning
confidence: 99%
“…Mater. Interfaces 2019 , 11 (35), 32408–32413, Copyright American Chemical Society) [ 54 ]; ( d ) thermal- and humidity-triggered response of zwitterionic SMP [ 61 ].…”
Section: Figurementioning
confidence: 99%